1997
DOI: 10.1109/20.617782
|View full text |Cite
|
Sign up to set email alerts
|

NiFe/CoFeB spin-valve heads for over 5 Gbit/in/sup 2/ density recording

Abstract: This paper outlines the successful use of NiFe/(Co90Fe10)ioo-~Bx (x = 5 1 0 % ) for soft magnetic, thermally stabilized spin-valves. The GMR effect in the NiFeKoFeB spinvalve increases after annealing. The annealing effect of CoFeB on CoFeB/Cu interfaces is investigated by high resolution TEM-EDX analysis. Merged inductive NiFe/CoFeB spin-valve heads with a read gap length of 0.18 pm and a write gap length of 0.28 pm having Ni0(400W)/NiFe(10~)/CoFeBs(lO~)/Cu(32~)/ CoFeBs(20A)/Ta(lOOW) spin-valve film and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…With this achievement, to obtain a recording density of 40-100 Gbit/in 2 using magnetic media is not just a dream in the near future. Significant progresses have also been made in the new generation of read head by using various types of GMR (giant magnetoresistive) spin valve multilayers [3][4][5][6] that fulfill the challenging requirements of reading process at high speed/frequency on high recording density media.…”
Section: Introductionmentioning
confidence: 99%
“…With this achievement, to obtain a recording density of 40-100 Gbit/in 2 using magnetic media is not just a dream in the near future. Significant progresses have also been made in the new generation of read head by using various types of GMR (giant magnetoresistive) spin valve multilayers [3][4][5][6] that fulfill the challenging requirements of reading process at high speed/frequency on high recording density media.…”
Section: Introductionmentioning
confidence: 99%
“…A small amount of B is added to Co 90 Fe 10 to improve the thermal stability. 14 We deposited the first two capping layers, Ta and Cu/Ta, by rf sputtering using Ar. We used a plasma oxidation method for the Cu/Al 2 O 3 capping.…”
Section: Methodsmentioning
confidence: 99%
“…Perpendicular magnetic anisotropy (PMA) in trilayers of nonmagnetic metal/ferromagnet/heavy metal (NM/FM/HM) or insulator/ferromagnet/heavy metal (I/FM/HM) is of great interest for spintronic applications such as spin-transfer-torque random access memory (STT-RAM), 1,2 magnetoelectric RAM, 3,4 and spin valves. [5][6][7][8][9] These perpendicularly magnetized heterostructures, where the NM and I layers are usually Cu and MgO, respectively, and the HM layer (Ru, Pd, Hf, Ta, Pt, Au) has strong spin orbit coupling (SOC), promise lower critical current for magnetization switching, faster magnetic switching, smaller magnetic bits, and high thermal stability. 1,9,10 Recently, it was shown that the material type and thickness of the HM layer play crucial role not only on the MA [11][12][13][14][15][16][17] but also on the voltage control 18 and magneto-transport behavior 7,14,16,19,20 of these trilayers.…”
Section: Introductionmentioning
confidence: 99%